(untitled) (International Seven Journal of Health Research, 2024)
Introduction: The practice of anesthesiology plays a crucial role in medicine, ensuring the comfort and safety of patients during medical and surgical procedures. However, this specialty faces a series of ethical and legal challenges. This article provides an overview of these issues, considering the importance of respecting patient autonomy and compliance with legal standards. Methods: To conduct this review, the following descriptors were used to search the PubMed and MEDLINE databases: "Anesthesiology", "Ethical", "Questions", "Aspects", "Legal". These descriptors were combined using the boolean operator AND to ensure search accuracy. Initially, 165 relevant studies were identified. After excluding duplicates, editorials, and incomplete articles, 122 articles were considered for analysis. The final selection included the full reading of 24 articles, of which 13 were considered relevant to compose this review. Results: Anesthesiologists face complex ethical dilemmas, from obtaining informed consent to making decisions in emergency situations. Additionally, there are concerns about fair resource allocation and balancing risks and benefits. In the legal realm, there are comprehensive regulations related to professional liability, documentation of procedures, and the use of medications and equipment. Conclusion: The practice of anesthesiology requires a solid understanding of the ethical and legal aspects involved. It is essential to respect patient autonomy by obtaining their informed consent. Constant ethical reflection and compliance with legal regulations are fundamental to ensuring the delivery of high-quality care.